Transformation and Overexpression of Primary Cell Wall Synthesis-Related Zinc Finger Gene Gh_A07G1537 to Improve Fiber Length in Cotton - Razzaq, Abdul; Zafar, Muhammad Mubashar; Li, Pengtao; Qun, Ge; Deng, Xiaoying; Ali, Arfan; Hafeez, Abdul; Irfan, Muhammad; Liu, Aiying; Ren, Maozhi; Shang, Haihong; Shi, Yuzhen; et al. (Frontiers in Plant Science, 2021)
Molecular interventions have helped to explore the genes involved in fiber length, fiber strength, and other quality parameters with improved characteristics, particularly in cotton. The current study is an extension and functional validation of previous findings that Gh_A07G1537 influences fiber length in cotton using a chromosomal segment substitution line MBI7747 through RNA-seq data. The recombinant Gh_A07G1537 derived from the MBI7747 line was over-expressed in CCRI24, a genotype with a low profile of fiber quality parameters. Putative transformants were selected on MS medium containing hygromycin (25 mg/ml), acclimatized, and shifted to a greenhouse for further growth and proliferation. Transgene integration was validated through Polymerase Chain Reaction (PCR) and Southern Blot analysis. Stable integration of the transgene (ΔGh_A07G1537) was validated by tracking its expression in different generations (T0, T1, and T2) of transformed cotton plants. It was found to be 2.97-, 2.86- and 2.92-folds higher expression in T0, T1, and T2 plants respectively of transgenic compared with non-transgenic cotton plants. Fiber quality parameters were also observed to be improved in the engineered cotton line. Genetic modifications of Gh_A07G1537 support the improvement in fiber quality parameters and should be appreciated for the textile industry.